A comparative study of single-dose esmolol and single-dose lignocaine in the prevention of intubation-induced tachycardia and hypertension during general anesthesia - Bandana Paudel,; Samir Ghimire,; Sumitra Paudel, (Asian Journal of Medical Sciences, 2022)
Background: During laryngoscopy and endotracheal intubation hemodynamic stress response is a great concern. Aims and Objective: This study aimed to compare single-dose esmolol with single-dose lignocaine in the prevention of intubation induced tachycardia and hypertension during general anesthesia. Materials and Methods: On 60 patients, a prospective comparative study was done. Patients ranging in age from 20 to 60 years old were included. Individuals with physical status I and II as per the guidelines of the American Society of Anesthesiologists (ASA) scheduled for elective surgeries under general anesthesia with endotracheal intubation were divided into two groups randomly. Two minutes before intubation, 1.5 mg/kg esmolol and 1.5 mg/kg lignocaine bolus doses were given diluted in 10 ml normal saline. Measurement of the mean heart rate (HR), the mean systolic blood pressure (SBP), and the mean diastolic blood pressure (DBP) was taken at the base level, during intubation and 1st, 2nd, 3rd,5th, and 10th minute after intubation. Also, mean arterial pressure was calculated based on these values. Results: The mean heart rate, systolic, diastolic, and mean blood pressure before starting anesthesia were similar in the Lignocaine group and Esmolol group (p>0.05). The mean heart rate (79.37±5.46 in lignocaine group and 74.63 ±5.411 in esmolol group), mean systolic blood pressure (127 ± 5.387 in lignocaine group and 114.50 ± 6.317 in esmolol group), mean diastolic blood pressure (83.07±3.028 in lignocaine group and 65.10 ± 2.77 in esmolol group) and mean arterial pressure (98.03±2.883 in lignocaine group and 81.57±2.812 in esmolol group) at intubation and 1,2,3,5 and 10 min after intubation showed a significant decrease in the values in the Esmolol group. Conclusion: Esmolol when given intravenously as a 1.5 mg/kg bolus dose, is proven to be superior and efficient in dampening the vasopressor response to laryngoscopy and endotracheal intubation in comparison with lignocaine given intravenously as 1.5 mg/kg bolus dose during general anaesthesia without inducing unexpected hypotension and bradycardia.